Conundrums in leishmaniasis. (September 2021) - Saha, Baibaswata; Bhattacharjee, Surajit; Sarkar, Arup; Bhor, Renuka; Pai, Kalpana; Bodhale, Neelam
Abstract: Parasites of the genus Leishmania cause the disease leishmaniasis. As the sandfly vector transfers the promastigotes into the skin of the human host, the infection is either cured or exacerbated. In the process, there emerge several unsolved paradoxes of leishmaniasis. Chronologically, as the infections starts in skin, the role of the salivary proteins in supporting the infection or the host response to these proteins influencing the induction of immunological memory becomes a conundrum. As the parasite invokes inflammation, the infiltrating neutrophils may act as "Trojan Horse" to transfer parasites to macrophages that, along with dendritic cells, carry the parasite to lymphoid organs to start visceralization. As the visceralized infection becomes chronic, the acutely enhanced monocytopoiesis takes a downturn while neutropenia and thrombocytopenia ensue with concomitant rise in splenic colony-forming-units. These responses are accompanied by splenic and hepatic granulomas, polyclonal activation of B cells and deviation of T cell responses. The granuloma formation is both a containment process and a form of immunopathogenesis. The heterogeneity in neutrophils and macrophages contribute to both cure and progression of the disease. The differentiation of T-helper subsets presents another paradox of visceral leishmaniasis, as the counteractive T cell subsets influence the curing or non-curing outcome. Once the parasites are killed by chemotherapy, in some patients the cured visceral disease recurs as a cutaneous manifestation post-kala azar dermal leishmaniasis (PKDL). As no experimental model exists, the natural history of PKDL remains almost a black box at the end of the visceral disease.